2014
DOI: 10.1080/21513732.2014.939719
|View full text |Cite
|
Sign up to set email alerts
|

The importance of climate variability changes for future levels of tree-based forest ecosystem services

Abstract: The climate is changing, yet to which degree and in what pattern remains uncertain in many areas. In forest science, mainly impacts of long-term mean changes in temperature and precipitation distributions are studied. This paper therefore presents a sensitivity analysis to determine the importance of accounting for variability changes. A 10*10 matrix of different mean annual temperatures and precipitation sums is set up, covering the temperate forest zone of Europe, and the current level of several ecosystem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In this Issue, Rasche (2014) presents a sensitivity analysis of the effects of climate variability on three supporting, regulating and cultural ES in temperate forests in Europe. Rasche (2014) found that variability of temperature and precipitation is especially important on moisture-limited and heat-stressed sites. The results underline the need to develop adaptation measures based on the ES of interest, and also show that even though trends are sufficiently described by changing climate variables, yet adaptive management requires the consideration of climate variability.…”
Section: Editorialmentioning
confidence: 99%
“…In this Issue, Rasche (2014) presents a sensitivity analysis of the effects of climate variability on three supporting, regulating and cultural ES in temperate forests in Europe. Rasche (2014) found that variability of temperature and precipitation is especially important on moisture-limited and heat-stressed sites. The results underline the need to develop adaptation measures based on the ES of interest, and also show that even though trends are sufficiently described by changing climate variables, yet adaptive management requires the consideration of climate variability.…”
Section: Editorialmentioning
confidence: 99%